THE URGENCY OF PRE-INTERNSHIP SOFT SKILLS TO PREPARE PROFESSIONAL HUMAN RESOURCES - Ayu Pratiwi; Munir Saputra (Adisam Publisher, 2025)
The internship program is one of the mandatory courses that students in college must undertake. With this internship program, students are expected to gain knowledge from the company where they are interning and be able to directly apply the theory gained in lecture activities. However, unfortunately, until now there are still many companies that complain about the poor behavior of students who take part in internships at their companies. Behavior related to soft skills. This research aims to answer the questions of how internship preparation is implemented by universities before students start their internship and what things that make companies often complain about the quality of students who take part in internships at their companies. This is qualitative research with a phenomenological approach. Data collection was carried out using semi- structured interviews with the head of human resources who periodically recruits students for internships. The research results show that the majority of students who take part in internship programs do not have adequate soft skills competencies. This can be seen from 4 (four) aspects, namely communication skills, critical thinking and problem solving skills, teamwork, ethics and morals.